Muqaran Tafsir Method: Its History, Basis and Implications - Wahid, Wahyu Muhammad Abdul; Kamils, Noor Muhamad Rizki (Jurnal Iman dan Spiritualitas, 2024)
Tafsir, examined in terms of its methods, is divided into two categories: general and specific methods. In general, discussions on the interpretation of the Qur'an can be conducted through four methods: Ijmali (global), tahlili (analytical), muqaran (comparative), and maudu'i (thematic). One of these four methods is the muqaran method, which means comparative or comparative analysis. The discussion of muqaran explains the comparison between one interpretation and another, whether related to Quranic verses with other Quranic verses, verses with hadiths, and the opinions of commentators. The purpose of this research is to present various opinions related to the muqaran method, its emergence, foundation, and urgency, as well as its steps and the strengths and weaknesses of muqaran interpretation. This research is qualitative and employs library research by referring to previous studies. The findings indicate that muqaran interpretation has been practiced since the time of Prophet Muhammad until the present day. Muqaran interpretation is also crucial for appreciating its inherent advantages.